VD_FINDINFO AI 31/10 - 2/2012 vom 23. Dezember 2011 - VD Tribunal cantonal (2011)
DEGRÉ DE L'INVALIDITÉ, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, RENTE D'INVALIDITÉ | 28 LAI, 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA